REVIU LAPORAN KEUANGAN PEMERINTAH DAERAH OLEH APARAT PENGAWASAN INTERN PEMERINTAH (APIP): STUDI PADA INSPEKTORAT PROVINSI SULAWESI UTARA - Pangemanan, Titof; Morasa, Jenny; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2023)
This study aims to analyze the role of the North Sulawesi gacorqq Provincial Inspectorate in improving the quality of LKPD, find out what obstacles are faced by the North Sulawesi gacorqq Regional Inspectorate in LKPD reviews to overcome repeated findings and to find out whether the review of LKPD conducted by the North Sulawesi Provincial Inspectorate has been effective. This study uses a qualitative method with a case study approach. Data obtained by in-depth interview techniques. To determine research informants, purposive sampling was used with the condition that they met the established criteria to obtain precise and accurate information. The results of the interviews were processed into data transcripts, then analyzed, coded and categorized into themes. Data analysis uses content analysis. The results of the study show that: (1) the role of the North Sulawesi Provincial Inspectorate in improving the quality of Regional Government Financial Reports is carried out by means of LKPD quality assurance, careful implementation of review stages and Review Work Programs, providing input and improvements to LKPD and preparation of quality Review Working Papers ; (2) the obstacles encountered in the LKPD review to overcome repeated findings were the limited review period, communication and coordination constraints between the LKPD Drafting Team (BKAD) and Regional Apparatus gacorqq Organizations, and lack of knowledge of financial management in Regional Apparatus Organizations due to employee mutations ; (3) the review conducted by the North Sulawesi Provincial Inspectorate was effective because in conducting the LKPD review the Regional Inspectorate had an attitude of independence and objectivity, besides that it was also supported by the competence of reviewers who had experience in the LKPD Review Team in previous years.